The concept of psychosocial in contemporary formation - Enas Ghazi Eidan; Sahib Jasim Hasan Al-Bayati (الاكاديمي)
The current research dealt with (the psychosocial concept in contemporary formation). The research included four chapters, the first chapter of which was concerned with the methodological framework of the research, represented by the research problem, which was determined by answering the following question: